The Exposition Medal Grand March - Adam Geibel::::::::: (J.M. Armstrong)
Piano score, 6 p. Cover title: Exposition Grand March, at head of title on cover: Presented to visitors, Centennial Exhibition, at Typographical Music Exhibit, Machinery Hall, North Avenue, Section E-5, Column 40. Publishers advertisement on verso of last leaf.